Solve This

[POD Archive] [Home]

Solve:

 

7n - 5(n - 3) = 3 - 4n

 

[click here for answer]

 

[POD Archive] [Home]

 

7n - 5(n - 3) = 3 - 4n      (convert to addition)

7n + (-5)(n - 3) = 3 - 4n  (distribute!)

7n + -5n + 15 = 3 - 4n    (combine like terms)

2n + 15 = 3 - 4n              (add 4n to both sides)

6n + 15 = 3                     (subtract 15 from both sides)

6n = -12                          (divide both sides by 6)

n = - 2                             (as they say in Boston!)